Structural, Optical and Gas Sensor Properties of Zinc Oxide Nanostructured thin films prepared by Chemical Spray Pyrolysis - I. Khudadad, Ameer; Abdoulsahib Eesee, Ezzulddin ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2025)
ZnO Nanostructured films were formed by chemical spray pyrolysis technique on stander glass (Made in China) substrate at (450oC). The structural and optical properties were studied in this research. The samples are a compound of pure (ZnO) with a hexagonal structure. X-Ray examination showed showing that the lattice parameters a= 3.286 Ao and c= 5.311 Ao. The average grain the size of crystals is on the order of (55nm), studying the topography of the surface by SEM, it appears that the growth of the thin film is very small nanoparticles, and there are also nanowires in it, which increases the region of the thin film’s surface. From the sake of studying the optical properties, Also, the absorbance factor was calculated for sample. energy gap for (ZnO) appeared to be about (3.25 eV), with direct band transitions. NH3 gas was used to measure the sensitivity of the thin film used in the study and the thin film was shown to have a high sensitivity to the gas.